2022
DOI: 10.3390/cancers14112784
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Therapeutic Efficacy of the PSMA Targeting Radioligand 212Pb-NG001

Abstract: This study aimed to determine the influence of cellular PSMA expression, radioligand binding and internalization, and repeated administrations on the therapeutic effects of the PSMA-targeting radioligand 212Pb-NG001. Cellular binding and internalization, cytotoxicity, biodistribution, and the therapeutic efficacy of 212Pb-NG001 were investigated in two human prostate cancer cell lines with different PSMA levels: C4-2 (PSMA+) and PC-3 PIP (PSMA+++). Despite 10-fold higher PSMA expression on PC-3 PIP cells, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
6
1
Order By: Relevance
“…Additionally, up to 80% free 212 Bi can also be conjugated (41). Similar binding and uptake abilities of the 212 Pb-labeled PSMA-targeting ligand NG001 in 224 Ra-solution or in 212 Pb-solution were observed in vitro and in vivo (41,56,57). Biodistribution studies of 224 Ra with free 212 Pb, 212 Pb-NG001, and 212 Pb-PSMA-617 were tested in athymic nude mice with C4-2 xenografts (41).…”
Section: Pb In One Solutionmentioning
confidence: 80%
“…Additionally, up to 80% free 212 Bi can also be conjugated (41). Similar binding and uptake abilities of the 212 Pb-labeled PSMA-targeting ligand NG001 in 224 Ra-solution or in 212 Pb-solution were observed in vitro and in vivo (41,56,57). Biodistribution studies of 224 Ra with free 212 Pb, 212 Pb-NG001, and 212 Pb-PSMA-617 were tested in athymic nude mice with C4-2 xenografts (41).…”
Section: Pb In One Solutionmentioning
confidence: 80%
“…In a study by Tschan et al, 161 Tb-labelled albumin-binder-conjugated PSMA-targeting agents demonstrated high tumour uptake and an enhanced tumour-to-kidney absorbed dose ratio [143]. Another study compared the dosimetry and therapeutic efficacy of 161 Tb and 177 Lu in tumour-bearing mice using SibuDAB and PSMA I&T [144]. 161 Tb decays with a similar half-life to 177 Lu, but in addition to the emission of β − -particles and γ-rays, 161 Tb also emits conversion and Auger electrons [144].…”
Section: Terbium: a Novel Nuclear Medicine "Swiss Army Knife"mentioning
confidence: 99%
“…Similar to the DOTAMTATE conjugate, a p -SCN-Bn-TCMC conjugated urea-based PSMA ligand has been studied for the diagnosis and therapy of prostate cancer. , Two research groups reported the synthesis and preclinical evaluation of p -SCN-Bn-TCMC-PSMA (NG001/CA09 , ). [ 212 Pb]­Pb­(NG001) compares well with [ 177 Lu]­Lu­(PSMA-617), with a greater potential to irradiate microscopic metastases. , …”
Section: The Rise Of Targeted α Particle Therapymentioning
confidence: 99%